Role Of Inflammatory Cells And Toll-Like Receptors In Atherosclerosis. - N Seneviratne, A; Monaco, C (2013)
Atherosclerosis is a multi-factorial inflammatory disease and is the primary initiator of cerebrovascular disease. At first many saw atherosclerosis as a lipid-driven disease. Recently inflammation has appeared as a significant factor in the disease. Innate immune cells, for example monocytes and macrophages, are important in atherosclerosis. Toll-like receptors (TLRs) are the most characterised innate immune receptors. TLR engagement with their ligands stimulate transcription of pro-inflammatory cytokines, foam cell formation and can activate adaptive immunity. Recently certain TLRs have shown a protective role in atherosclerosis. In this review, we analyse the role of innate immunity, specifically macrophages and TLR signalling, in atherosclerosis and acute cerebrovascular complications, and thereby discuss the potential of TLRs to act as therapeutic targets.